(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
The idea of a syntaxonomic class at the current level of development of the vegetation science has been considered. We analyzed the classical definition of the class provided by J. Braun-Blanquet as well as the criteria of the class, which were mentioned and applied by various authors during the phytosociology development: floristic, ecological, physiognomic, chorological, evolutionary, and applicable. When considering the floristic criterion, we paid attention on the concept of absolute diagnostic species and illustrated existing problems in distinguishing and recognition of some vegetation classes of Ukraine, as well as the problem of class inflation by examples from recently published syntaxonomic surveys of Europe and Ukraine. We developed the modern ideas about the spatial arrangement of phytocenoses and their scale dimensions. The presented review demonstrated that the main approach to distinguishing the vegetation class should remain floristic and sociological. Other criteria can serve as additional arguments when delineation borders in vegetation continuum, checking working hypotheses and making syntaxonomic decisions, especially in cases where the object of research is located in a comprehensive multidimensional space. Ecological, physiognomic, chorological, evolutionary as well as applicable criteria should not play a key role and logically correlate with the floristic criterion. We tried to prove the fallacy of listing Poetea bulbosae and Saginetea maritimae classes for Ukraine based on the analysis of compliance with the main criteria for class recognition. Different approaches to dividing classes into groups according to their quality have been also considered. We assume that over the next decade, increasing the representativeness of phytosociological data for Ukraine and Europe will allow an objective assessment of the quality of vegetation classes using statistical methods.